2012
DOI: 10.1111/j.1365-2702.2012.04282.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an individual sleep intervention programme in people undergoing peritoneal dialysis treatment

Abstract: Aims and objectives This study aimed to evaluate effects of a non‐pharmacological intervention on sleep, activity and fatigue in patients receiving peritoneal dialysis by the use of both actigraphy registration and self‐assessed questionnaires. Background Insomnia is estimated to affect up to 60% of haemo‐ and peritoneal dialysis patients. It is associated with two common uremic symptoms, pruritus and restless legs syndrome. To our knowledge, no interventions have been evaluated by actigraphy. Design A prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Cognitive-behavioral therapy (CBT) for sleep disturbances in dialysis patients has shown promising effects on fatigue, with modest but significant reductions in fatigue scores after intervention. 118,119 A very small individual sleep intervention study by Yngman-Uhlin et al 66 also revealed similar results, with four out of nine patients reporting reductions in fatigue. Although these findings corroborate the association between sleep problems and fatigue, larger investigations are needed to support these data.…”
Section: Nonpharmacological Treatment Of Fatigue In Renal Patientsmentioning
confidence: 68%
See 1 more Smart Citation
“…Cognitive-behavioral therapy (CBT) for sleep disturbances in dialysis patients has shown promising effects on fatigue, with modest but significant reductions in fatigue scores after intervention. 118,119 A very small individual sleep intervention study by Yngman-Uhlin et al 66 also revealed similar results, with four out of nine patients reporting reductions in fatigue. Although these findings corroborate the association between sleep problems and fatigue, larger investigations are needed to support these data.…”
Section: Nonpharmacological Treatment Of Fatigue In Renal Patientsmentioning
confidence: 68%
“…64 Joshwa et al 36 reported an association between daytime sleepiness, poor night-time sleep, and fatigue; results that were supported in both HD 50,65 and PD patients. 66,67 In addition, Sanner et al 15 found that the severity of sleep-related breathing disorders was associated with levels of vitality.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Relatively few studies have investigated the efficacy of sleep hygiene interventions in nonclinical samples. 16-20 Overall, this work has provided some preliminary support for the use of sleep hygiene education in nonclinical populations, but the findings are inconsistent. Taken together with findings in clinical samples, these data raise an interesting question.…”
mentioning
confidence: 89%
“…Although there was no significant difference in the severity or frequency of pruritus between the 3 study groups, itch-associated insomnia was significantly more common in patients on PD [1][2][3]. Although we have no clear explanation for this finding, there are many reports of insomnia in patients on dialysis, particularly those performing automated PD [4][5][6]. Moreover, the dialytic efficiency of PD is less than that of HD, so it is possible that patients on PD are more likely to become uremic and therefore are more prone to uremic pruritus.…”
Section: Discussionmentioning
confidence: 44%